Skin friction calculation for PU/PIR against steel duct using CFD - Munisamy K.M.; Yusoff Mohd.Z.; Soon S.P.; Cheong P.W. (2023)
The PU/PIR duct has texture of 0.5mm height along the duct. This study focus on the frictional loss of flow through a rectangular duct of PU/PIR duct. As a compariosn a steel duct with surface roughness is also simulated. The duct considered in this study has a cross-section of 300mm X 300mm and length of 1500mm. The two designs are simulated in FLUENT proprietry software. The Hybrid tetrahedral element grids are used in building non-uniform mesh. The total computational nodes involved in the calculation are about 3 million cells. This is due to the small geometry of the PU/PIR duct texture at the wall. The appropriate boundary setting and numerical setting is explained in proceeding section. The geometry generated is then simulated for 200CFM, 400CFM, 800CFM, and 1200CFM flow conditions. (CFM = cubic feet per minute) The mesh generated and the results are presented. The coefficient of friction is calculated from CFD and plotted. The velocity and pressure distribution are also illustrated for all CFM simulated. 2009 IEEE.